Beispiel Nr: 22
$ D_h=\begin{array}{|cc|}a1\ & b1 \\ a2&b2 \\ \end{array}= a1 \cdot b2 -b1 \cdot a2 \\ D_x=\begin{array}{|cc|}c1\ & b1 \\ c2&b2 \\ \end{array}= c1 \cdot b2 -b1 \cdot c2 \\ D_y=\begin{array}{|cc|}a1\ & c1 \\ a2&c2 \\ \end{array}= a1 \cdot c2 -c1 \cdot a2\\ x=\frac{D_x}{D_h} \\ y=\frac{D_y}{D_h} \\ \\ \textbf{Gegeben:} \\ \\ -7 x +9 y =-3\\ 5 x -6 y = -4 \\ \\ \\ \\ \textbf{Rechnung:} \\ D_h=\begin{array}{|cc|}-7\ & 9 \\ 5&-6 \\ \end{array}= -7 \cdot \left(-6\right) -9 \cdot 5=-3 \\ D_x=\begin{array}{|cc|}-3\ & 9 \\ -4&-6 \\ \end{array}= -3 \cdot \left(-6\right) -9 \cdot \left(-4\right)=54 \\ D_y=\begin{array}{|cc|}-7\ & -3 \\ 5&-4 \\ \end{array}= -7 \cdot \left(-4\right) -\left(-3\right) \cdot 5=43 \\ \ x=\frac{54}{-3} \\ x=-18 \\ y=\frac{43}{-3} \\ y=-14\frac{1}{3} \\ L=\{-18/-14\frac{1}{3}\}\\ \, $